Avaliação de desempenho e conforto térmico de habitações multifamiliares em clima quente e úmido - Silva, Luis Anderson Conceição da (2019)
The study of thermal performance and thermal comfort for vertical walls in naturally ventilated multifamily residential buildings is fundamental for the building industry, as it has great potential for energy rationalization and provides indoor environments with better user satisfaction. In Brazil, the methodology for thermal performance evaluation for social housing is presented in ABNT NBR 15575-1: 2013 - Housing Buildings - General Requirements. However, the Brazilian standard is still very simplified and does not take into account thermal adaptive indices and real measurements in buildings. The present work aims to analyze and evaluate the performance and thermal comfort of vertical walls systems of multifamily residential habitations, applying the (informative) measurement method prescribed by ABNT NBR 15575: 2013 performance standard for solid wall construction systems, concrete block structural and ceramic block structural. Perform numerical simulation method for adaptive thermal comfort analysis of these building systems in the hot and humid climatic context. These 03 construction systems were defined for data collection and evaluation of thermal performance and thermal comfort, and for numerical modeling. The data collection had as environmental parameters of temperature measurement (internal and external) and relative humidity of the air. For the constructive systems evaluated in this work, it is noted that the criterion of the informative procedure of measurements (maximum internal temperatures lower than the maximum external temperatures) of ABNT NBR 1557: 2013 is difficult to be met most of the time. The simulation procedure in force in the Brazilian standard does not consider important parameters that influence the thermal performance of residential buildings, such as internal thermal loads and natural ventilation. The typical day is vulnerable due to method uncertainties, mainly caused by inaccuracies and lack of data in ABNT NBR 15575: 2013. Adaptive modeling, using operating temperature and occupation parameters, are indicated in analyzes and studies that approximate the reality of operation of housing units. The thermal transmittance of the building systems and the absorbance of the components have a great influence on the thermal comfort results in the adaptive approach of this study.